Embedded Electricity Quality Analyzer - Freitas, S. (2019)
Electric installations are traditionally designed for supplying an electric service. The only one associated instrument is the energy meter that is introduced only for measure the total amount of energy that will be charged to the user. However, the exploration of parameters associated with electricity can provide several advantages such the household performance devices, legal issues and later one a more sustainable way to use the electricity energy. This work presents the principle of a low cost energy analyzer that will be part of an electric home installation. Electric parameters are measured and then transmitted via Wi-Fi to a domestic server where all data are stored. This data exploitation can be later one used for several purposes, since electric efficiency to electric charges prediction.